COMPARATIVE STUDY ON THE PILATES AND EGOSCUE EXERCISE FOR CORE MUSCLE STRENGTHENING AND POSTURAL CORRECTION TO BICYCLE RIDERS WITH LOWBACK PAIN AMONG SCHOOL STUDENTS - Shanmugananth Elayaperumal, Arun Jenikkin. A, Muthukumaran jothilingam, Abishek Godwin, Subramania Bharathy Sivashankaran, Faith Sajith, Kshtrashal Singh (South Eastern European Journal of Public Health, 2025)
Background: Low back pain is a pervasive and debilitating condition affecting millions of individuals worldwide, particularly among school going students. The prevalence of LBP among school-aged children has been reported to range from 30% to 60% Purpose Of The Study: To compare the effectiveness of Pilates and Egoscue exercise for core muscles strengthening and postural correction to bicycle riders with low back pain among school students. Aim: To compare the effectiveness of Pilates and Egoscue exercise for core muscles strengthening and postural correction to bicycle riders with low back pain. Methods: A total of 40 subjects were randomly assigned to Group A and B. Group A performed Pilates exercise. Group B performed egoscue exercise. 4 sessions per week of 4 weeks of duration. Conclusion: the study concluded that Pilates Exercise reduces pain and increases functional ability then Egoscue exercise among the school student with Low Back Pain in Bicycle Riders.